Teacher perceptions and promotion of academic honesty: A qualitative case study of humanities teachers within a Diploma Program (DP) at one International Baccalaureate (IB) school in Kazakhstan - Altaibekova, Magripa (Nazarbayev University Graduate School of Education, 2020)
The concept of academic honesty is a common educational issue throughout the world. In International Baccalaureate (IB) Programmes, academic honesty is particularly vital. It is expected that educational stakeholders, including students and teachers, should follow and promote academic honesty. However, internationally there are still concerns of understanding and promoting academic honesty consistently. In Kazakhstan, the term academic honesty is not widely used, understood, or applied. Therefore, to address this relatively new concept, this thesis study explores how academic honesty is perceived and promoted by humanities teachers of the Diploma Programme (DP) at one IB school in Kazakhstan. I used a qualitative research design in order to answer the following research questions: How do DP humanities teachers perceive academic honesty at one IB school in Kazakhstan? What practices do DP humanities teachers use in the classroom to promote student academic honesty at one IB school in Kazakhstan? Data collection included one-to-one semi-structured interviews and curriculum documents. Analysis included coding and transcribing interviews and document analysis of the curricula provided by the participants. The study was conducted by the conceptual framework of socio-cultural theory, which helped to develop and plan all parts of this study. Insights can be useful both for the specific school and also for future studies to address issues of academic honesty and the related concept, academic misconduct. Future research on academic honesty are also suggested to include additional stakeholders to provide a picture of an entire school, as well as challenges and successes in promotion of academic honesty from different perspectives.
Teacher perceptions and promotion of academic honesty
Keywords: academic honesty, teacher perception, teacher promotion, humanities, qualitative research, International Baccalaureate, Diploma Programme, Kazakhstani teachers